1994
DOI: 10.1128/mcb.14.9.6386
|View full text |Cite
|
Sign up to set email alerts
|

A novel DNA replication origin identified in the human heat shock protein 70 gene promoter.

Abstract: A general and sensitive method for the mapping of initiation sites of DNA replication in vivo, developed by Vassilev and Johnson, has revealed replication origins in the region of simian virus 40 oyi, in the regions upstream from the human c-myc gene and downstream from the Chinese hamster dihydrofolate reductase gene, and in the enhancer region of the mouse immunoglobulin heavy-chain gene. Here we report that the region containing the promoter of the human heat shock protein 70 (hsp7O) gene was identified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 37 publications
2
39
0
2
Order By: Relevance
“…Expression of wild-type Nbs1 in NBS-deficient cells reduced the percentage of cells with more than four dots by more than fourfold ( Table 1A). Probes that recognize DNA regions containing known sites of DNA synthesis initiation near the HSP70 and Lamin B2 genes (Taira et al 1994;Abdurashidova et al 2000) yielded similar results (data not shown). Almost all NBS-deficient cells (GM07166) were characterized by normal chromosomal numbers.…”
Section: Nbs Deficiency Leads To Reinitiation Of Dna Replication At Rsupporting
confidence: 72%
“…Expression of wild-type Nbs1 in NBS-deficient cells reduced the percentage of cells with more than four dots by more than fourfold ( Table 1A). Probes that recognize DNA regions containing known sites of DNA synthesis initiation near the HSP70 and Lamin B2 genes (Taira et al 1994;Abdurashidova et al 2000) yielded similar results (data not shown). Almost all NBS-deficient cells (GM07166) were characterized by normal chromosomal numbers.…”
Section: Nbs Deficiency Leads To Reinitiation Of Dna Replication At Rsupporting
confidence: 72%
“…When the canonical cmyc-responsive element (CACGTG) of the ornithine decarboxylase (a myc target gene) promoter was replaced by the non-canonical element, the modi®ed promoter was even more responsive to c-myc. A similar or identical non-canonical myc-responsive sequence has also been identi®ed in the promoters of other genes such as HSP70 (Taira et al, 1994), c-myc itself (Ariga et al, 1989), and in the EFII enhancer of the Rous sarcoma virus LTR (Hann et al, 1994). Interestingly, the physiological importance of this myc-responsive element is further supported by the observations that the non-canonical sequence exhibits binding to in vivoderived Myc protein (Hann et al, 1994) and it e ciently binds to Myc ± Max heterodimers, but not to either Myc or Max homodimers (Hann et al, 1994;Kasibhatla et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Nine replication origins were examined: namely, those situated near the genes MCM4 (13), HSPA4 (14), TOP1 (15), MYC (16), SCA-7 (17), AR (17), DNMT1 (18), LaminB2 (19), and ␤-globin (20).…”
Section: Methodsmentioning
confidence: 99%